Association of comorbidities with clinical outcomes in patients after acute myocardial infarction. (August 2020) - Baechli, Ciril; Koch, Daniel; Bernet, Selina; Gut, Lara; Wagner, Ulrich; Mueller, Beat; Schuetz, Philipp; Kutz, Alexander
Abstract: Background: Multimorbidity becomes more prevalent in patients admitted for acute myocardial infarction (AMI). We investigated the association of an increasing number of comorbidities with the excess risk of in-hospital mortality and other clinically outcomes in hospitalized AMI patients. Methods: In this population-based cohort study, we analyzed 104'906 admissions for AMI between 2012 and 2018 in Switzerland. We stratified patients based on four different age categories and investigated the association of the number of five common comorbidities (diabetes, chronic kidney-, chronic obstructive pulmonary-, cerebrovascular-, and peripheral artery disease) and risk of in-hospital mortality and other outcomes. Results: A total of 5'029 admitted AMI patients (4.8%) died during the hospital stay. We found a stepwise increase in mortality risk with each additional comorbidity. Compared to AMI patients with no comorbidity, comorbid patients had a 26% increased risk for mortality (adjusted odds ratio [OR] 1.26, 95% confidence interval [CI] 1.20 to 1.33) with a pronounced association in younger patients. The overall risk for ICU admission, prolonged length of hospital stay (LOS), and 30-day readmission was higher in comorbid patients as compared to those without a comorbidity of interest (ICU: OR 1.19, 95% CI 1.16 to 1.22; LOS: OR 1.84, 95% CI 1.79 to 1.89; Readmission: OR 1.23, 95% CI 1.19 to 1.28), respectively. Again, the association of the numbers of prevalent comorbidities with adverse outcomes was strongest in the youngest patient population. Conclusions: In patients with AMI, the burden of comorbidities has a strong association with in-hospital mortality and other adverse outcomes – especially in younger patients.